Fellingsdams : an investigation of wastewater treatment by chemical precipitation in ponds in northern Sweden - Zhang, Wen (2008)
Fellingsdams are widely used in northern Sweden as an economical and easy operating method to treat the wastewater. They are divided into in-pond and pre-pond systems by different locations of dosage. Aluminium salts, iron salts and slaked lime are the most common coagulants that have been used, since they are cheap and easy to react with water. Turbidity and detention time are two important factors in fellingsdams. Turbidity is mainly influenced by precipitation and algae. From the perspective of actual detention time, the pond geometry should be long and narrow. When using slaked lime as coagulant, there is usually a large amount of sludge accumulated around the influent pipe because of fast precipitation. In the fellingsdam at Nyliden, 90% of the total sludge was found accumulated in about 20 meters. Aluminium salts and iron salts react slower with water, so the formed sludge curves are modest. To remove the sludge, excavation and pumping are the choices but differs due to different conditions. Dewatering is the main way to treat the sludge. The main task for a fellingsdam is to remove the organic carbon, nitrogen and phosphorus. The effluent values from yearly environmental reports 2001- 2007 were analyzed, most values were below the demands. The coliform bacteria concentration is a problem in the effluent water. A high pH environment guarantees low bacteria concentration in the effluent. Laboratory analyses were made on samples from a few aluminium fellingsdams and iron fellingsdams, only the pond in Hede reduced the coliform bacteria concentration below 10 cfu/100ml. Mellansel fellingsdam, an iron pond, had a high value of 6600 cfu/100ml in the effluent. Future utilization of the effluent water is also discussed: irrigation is one of the uses. The energy forest in Vika Strand, Falun is a good example. Validerat; 20101217 (root)